KEWENANGAN PEMERINTAH DAERAH DALAM PEMAJUAN KEARIFAN LOKAL BIDANG KEBUDAYAAN DI KABUPATEN PADANG PARIAMAN - Syarif, Muhammad; Syofiarti, Syofiarti (UNES Law Review, 2023)
The people of Padang Pariaman, who are so diverse in culture, certainly have the potential to be influenced by foreign cultures in the era of globalization and modern developments at this time, Padang Pariaman culture broadly consists of religion or belief, a system of community organizations, a system of knowledge (education), language, arts, livelihood systems. This is what contains a lot of local wisdom in it. In the current condition, culture is starting to be abandoned, even some Indonesian people are ashamed of their culture as a nation's identity. The differences that occur in Indonesian culture are due to different growth processes and influences from other cultures that mix in it. The sharing of laws also mentions culture and indigenous peoples, including in Article 1 paragraph (3) of Law No. 5 of 2017 concerning the Advancement of Culture, the promotion of culture is an effort to increase cultural resilience and Indonesia's cultural contribution to the midst of world civilization.